The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1590/2236-8906-52/2013
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric pollen and spore content in the urban area of the city of Medellin, Colombia

Abstract: -(Atmospheric pollen and spore content in the urban area of the city of Medellin, Colombia). The atmosphere of the urban area of the city of Medellin, Colombia was monitored with the objective of identifying airborne pollen and spores throughout a whole year. Sampling was performed between February 2010 and March 2011, coinciding with the La Niña climate phenomenon, which is characterized by a considerable increase in precipitation. Samples of airborne spores and pollen were obtained from a suction Hirst-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 16 publications
(16 reference statements)
1
8
0
4
Order By: Relevance
“…BioLNA ranged between 6.8×10 2 and 2.9 ×10 4 m -3 (average: 1.1×10 4 m -3 ; CV: 20%), HNA(fungal spores) between 4.7×10 and 1.9×10 4 m -3 (average: 1.1×10 m -3 ; CV: 15%) when above the detection limit (n=12), and pollen from 1.3×10 to 1.2×10 m -3 (average: 3.6×10 2 m -3 ; CV: 21%). These concentration levels are consistent with microscopy-based studies in urban environments for bacteria (e.g., 1.7×10 4 ± 1.3×10 4 m -3 in springtime Birmingham, UK; (Harrison et al, 2005); fungal spores (1.8×10 4 ± 1.1×10 4 m -3 in Vienna, Austria between April-June; ; and pollen (between 5.69×10 2 m -3 to 6.144×10 3 m -3 in Medellin, Colombia; Guarín et al, 2015). Also, additional experiments performed in September 2015, described in Figure S7 of the supplemental information (supplemental information, SI.6), showed that EPM and FCM-based quantifications agree within an order of magnitude.…”
Section: Fcm Biopopulation Identification and Quantificationsupporting
confidence: 88%
“…BioLNA ranged between 6.8×10 2 and 2.9 ×10 4 m -3 (average: 1.1×10 4 m -3 ; CV: 20%), HNA(fungal spores) between 4.7×10 and 1.9×10 4 m -3 (average: 1.1×10 m -3 ; CV: 15%) when above the detection limit (n=12), and pollen from 1.3×10 to 1.2×10 m -3 (average: 3.6×10 2 m -3 ; CV: 21%). These concentration levels are consistent with microscopy-based studies in urban environments for bacteria (e.g., 1.7×10 4 ± 1.3×10 4 m -3 in springtime Birmingham, UK; (Harrison et al, 2005); fungal spores (1.8×10 4 ± 1.1×10 4 m -3 in Vienna, Austria between April-June; ; and pollen (between 5.69×10 2 m -3 to 6.144×10 3 m -3 in Medellin, Colombia; Guarín et al, 2015). Also, additional experiments performed in September 2015, described in Figure S7 of the supplemental information (supplemental information, SI.6), showed that EPM and FCM-based quantifications agree within an order of magnitude.…”
Section: Fcm Biopopulation Identification and Quantificationsupporting
confidence: 88%
“…Los 11 géneros que se identificaron por ambos sistemas volumétricos, se citaron anteriormente en estudios ambientales cubanos de exteriores, en los que también se reflejó a Cladosporium, Aspergillus y Penicillium como abundantes (Almaguer et al 2012. Similares resultados se registraron en República Dominicana (Landa et al 2015), Colombia (Alzate et al 2015) y México (Rocha et al 2013).…”
Section: Discussionunclassified
“…Diferentes autores han encontrado una variación en la concentración de esporas respecto a las condiciones meteorológicas. (Quintero et al, 2010;Almaguer et al, 2013;Almaguer et al, 2015;Guarín et al, 2015). Así, Lin & Li (2000) investigaron las relaciones entre la concentración de esporas y las condiciones meteorológicas.…”
Section: Discussionunclassified